GELATIN IKAN DAN PEMANFAATANNYA - Achmad Muflih (Samakia : Jurnal Ilmu Perikanan, 2014)
Demand for Industrial gelatin in Indonesia is increasing, This is because gelatin widely used by the pharmaceutical industry, food and non food. In 2002 the import demand gelatin for industry reached 2,144 tons and in 2003 increased to 6,233 tons. Statistical data in January-Desmber 2009, the government imported gelatin amounted to 3,124,255 kg with the import value reached US $ 16,741,918. Gelatin is imported from countries China, Japan, Germany, France da Australia. Gelatin is imported by the government are produced from raw materials pigskin, cowhide and cow bones. Gelatin is a result of hydrolysis of fish protein in fish bone, fish skin.